Artificial Intelligence tools perceptions: A survey to measure the Perceptions of Engineering Students - Al-Falahat, Ala’a M. (International Journal of Innovative Research and Scientific Studies, 2025)
This research intends to evaluate the usage and impact of Artificial Intelligence (AI) in engineering education through a cross-sectional study using a web-based questionnaire distributed to 290 undergraduate and graduate students. The objective is to assess the students' perceptions toward AI tools, which AI uses in their education and future jobs, its prospects and challenges, and their experiences with AI applications. The results indicated high acceptance of general-purpose AI applications in engineering, such as ChatGPT (50.7% regular use) and Grammarly (65.9%), while lower acceptance exists for specialized AI applications in engineering. Students see the use of AI as beneficial for improving academic performance, especially in writing technical reports (94.1% agreement) and research (86.6% agreement). The study found that 87.6% of students agreed that AI gives them an edge in courses and projects. However, 65.5% of the respondents were concerned about ethics and felt traditional skills in problem-solving should be upheld. Attitudes toward AI tools and the way they are used showed statistically significant differences across academic levels and years in the program, pointing toward the necessity of tailored teaching methods. While underlining the transformative potential of AI in engineering education, the study emphasizes the need to address ethical considerations and find a middle ground between promoting AI-assisted learning and developing traditional skill sets.